Efficacy of modified technique for 1 cm core needle biopsy using a 2 cm cutting length with coaxial introducer needle. - Satomura, Hiroki; Kimura, Yasushi; Nakamura, Masahisa; Tomotake, Kosuke; Yamamoto, Koki; Tanaka, Kaishu; Ono, Yusuke; Higashihara, Hiroki; Tomiyama, Noriyuki (Abdominal Radiology, 2025)
Purpose: This study evaluated the efficacy of a modified core needle biopsy using a 2 cm stroke length to improve tissue yield for molecular analyses in cancer genomics medicine. Methods: In vitro biopsy weight evaluations were performed using agarose gels of varying hardness. Ex vivo biopsy weight evaluations were conducted using chicken liver, gizzard, breast, and pork loin tissues. Furthermore, in vivo experiments were performed using murine subcutaneous tumor models. The modified method involved using a coaxial introducer needle to maintain a 1 cm notch length while employing a 2 cm stroke length to increase tissue yield. Biopsy performance parameters, including sample weight and DNA yield, were compared between the modified and conventional methods. The firing speed of the biopsy needles with 1 cm and 2 cm stroke lengths was also measured using a high-speed camera. Results: The modified technique significantly increased the sample volume across all agarose gel concentrations (9.5–13% increase, P < 0.05). Ex vivo tests revealed significantly higher tissue yields in most samples, except for chicken gizzards. In vivo, the modified method produced significantly larger tissue samples (4.6 mg vs. 2.9 mg, P < 0.001) and higher DNA yield (8.2 ng vs. 6.9 ng, P < 0.05). In addition, the biopsy needle's firing speed was 1.4–1.8 times faster with the 2 cm stroke length than 1 cm stroke. Conclusion: The modified biopsy technique using a 2 cm stroke length significantly improved tissue yield, enhancing the quality of biopsy samples for molecular analyses in precision medicine.